Improving The Religious Character of Educators Through Exemplary of Principles - Indawati, Ninik; Kartiko, Ari; Suyitno, Suyitno; Sirojuddin, Akhmad; Fuad, Zaqiatul (JURNAL AL-TANZIM, 2022)
This paper aims to analyze the principal's good strategy in improving the religious character of teachers and education personnel at SDN 2 Mimbaan Situbondo. This paper uses qualitative research with a case study approach. The data collection technique was carried out with participatory observation, unstructured interviews, and documentation. Data analysts follow the Huberman model. The findings of this article are: 1) Forms of exemplary principles in improving the religious character of teachers, namely; honest, disciplined, fond of worship, trust, and responsibility; 2) Implementation of exemplary principles in improving the Islamic character of educators with stages of value transformation, value transactions and value transinternalization. This research implies that the principal has a positive effect on all school members with the exemplary model that is exemplified.